2019
DOI: 10.1016/j.foodpol.2019.03.005
|View full text |Cite
|
Sign up to set email alerts
|

What drives smallholder farmers’ willingness to pay for a new farm technology? Evidence from an experimental auction in Kenya

Abstract: Highlights Demand among smallholder farmers in Kenya for improved storage bags is elastic. Lowering the price of the bag by 20% leads to a 29% increase in profit. Prior awareness of the technology increases mean willingness to pay by 20%. Medium by which information is disseminated does not affect willingness to pay. Cheapest media option, text message, is most cost-effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 28 publications
3
25
0
1
Order By: Relevance
“…It seems that innovation adoption decisions are strongly influenced by farmers' exposure to and awareness of the benefits of the technology (Rogers, 1983). Our finding is consistent with Channa et al (2019) and Qaim and De Janvry (2003). For the sensor arrays, however, the estimated coefficients for tool knowledge were insignificant.…”
Section: Household Characteristicssupporting
confidence: 89%
See 1 more Smart Citation
“…It seems that innovation adoption decisions are strongly influenced by farmers' exposure to and awareness of the benefits of the technology (Rogers, 1983). Our finding is consistent with Channa et al (2019) and Qaim and De Janvry (2003). For the sensor arrays, however, the estimated coefficients for tool knowledge were insignificant.…”
Section: Household Characteristicssupporting
confidence: 89%
“…New agricultural innovations are key for improving productivity and profitability and achieving sustainable development (Channa et al, 2019), especially in developing countries (Doss, 2006;Feder et al, 1985). Studies suggest that the uptake of innovation is a dynamic process through which individuals gradually learn about an innovation and adopt it (Baumüller, 2012).…”
Section: Agricultural Technology Adoption Theorymentioning
confidence: 99%
“…One of the lessons from experimental economics is that the closer researchers approach real transactions, the more likely respondents will express their true preferences. Previous studies of the value of grain moisture information and measurement devices have demonstrated devices and elicited preferences (Shinamoto et al, 2017;Channa et al, 2018). This study goes beyond previous studies in that grain moisture measurement devices were sold to farmers who pay with their own funds.…”
Section: Methodsmentioning
confidence: 82%
“…800 Taka) for a grain moisture meter. Moisture meter sales were mostly to farmers with over 1.2 hectares of land and several tons of rice production annually Channa et al (2018). reported a willingness to pay by Kenyan farmers of an average of US$1.20 for a hygrometer that can measure the temperature (T) and relative humidity (RH) of the air around the grain.…”
mentioning
confidence: 99%
“…We make several contributions to the literature on adoption of welfare enhancing technologies, and in particular yield enhancing technologies. Our main contribution to the literature is on information barriers to adoption of agricultural technologies and the role certification could play for signalling quality of a credence good (Fuglie et al ., 2006; De Groote, 2011; Guei et al ., 2011; Banerji et al ., 2016; Poku et al ., 2018; Channa et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%